The Role of Prices, Locations, and Promotions on Smartphone Purchase Decisions in Electronics Shop in Indonesia: a Lesson from Sidoarjo - Shinta Devi; Slamet Harjatno (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effect of price, location and promotion simultaneously and partially to the decision to purchase a smartphone in JH Phone Sidoarjo and to find out the most influential variables on purchasing decision. Hypothesis testing using simultaneous test (F test) and partial test (t test) by using program SPSS version 18.0.The results of research based on Validity Test showed that all research instruments is valid because it has a value of r arithmetic > r table. Based on hypothesis test result showed that the price, location and promotion simultaneously have a significant effect on the decision of purchasing a smartphone in JH Phone Sidoarjo. Hypothesis test results also showed that the price, location and promotion partially have a significant effect on the decision to purchase a smartphone in JH Phone Sidoarjo.